Improving data use in decision-making and utilization of maternal healthcare services through a data-informed platform for health approaches in districts of the Gedeo Zone, southern Ethiopia, 2023: a cluster-randomized control trial - Zenebe, Getachew Assefa; Alemu, Wagaye; Yehualashet, Daniel; Nakachew, Mequanint (Frontiers in Health Services, 2023)
In low-resource countries like Ethiopia, the utilization of local data for planning and decision-making health system is frequently constrained. In addition, despite several government initiatives, maternal health services were not completely utilized. On the other hand, not enough has been done to effectively utilize the local data that is available to improve the utilization level of maternal healthcare services, necessitating the need for a different approach.Objective: This implementation study aims to test and validate the effectiveness of a datainformed platform for health strategy on data use for decision-making and utilization of maternal health services in districts of Gedeo zone, Southern Ethiopia.Methods: A two-arm parallel groups, type II hybrid, cluster-randomized control trial (C-RCT) design will be applied to conduct the study from September 1/ 2022 to February 30/ 2024. Six Woredas/districts will be assigned as an intervention arm and the other six for control arm.Baseline and end line data will be collected from 120 eligible health management staff (both intervention and control arm). In the intervention arm, district health management staff will be given special training and continuous technical assistance as a package called the data-informed platform for health (DIPH) strategy by embedding it with district's current decision-making platform such as Performance Review Team (PRT) meetings. The DIPH strategy mainly focuses on five-step approaches such as situational assessment, stakeholder engagement, define/priority setting, plan, and follow-up. Health management staff in the control arm will only function in their day-to-day activities. Chi-square and t-test will be used to check the effect of the intervention. In addition, difference-in-differences estimates will be done because the change may inherently happen over time. A P-value of < 0.05 and a 95 percent confidence interval (CI) will be used to declare the significance of the intervention.The findings of this study are supposed to give insights into implementation strategies for policymakers and stakeholders to improve data use in decision-making and utilization of maternal healthcare services at the Woreda level as well as to uncover contextual factors that boost the response of these strategies.